2011
DOI: 10.1017/s1368980011000541
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviour and its association with social living conditions and weight status among adolescent girls: results of the cross-sectional Berlin School Children's Cohort study

Abstract: Objective: To capture a more holistic picture of eating behaviour by investigating the impact of the social living conditions and weight status of parents and daughters on food consumption frequency, the context of meals and daily portion sizes. Design: Cross-sectional Berlin School Children's Cohort study. Setting: A total of sixty-nine schools in Berlin (3 400 000 inhabitants, eastern Germany) participated in the present study. Subjects: A total of 1519 girls aged 11-14 years were selected. Bi-and multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 43 publications
1
25
3
1
Order By: Relevance
“…'Overweight in parents' was relevant because among non-consumers of legumes were found more frequently obese or overweight subjects. Moreover numerous studies have shown that overweight in parents influences the child's eating behavior [18]. In our study individuals who practice physical activities consumed more frequently legumes, on the contrary smokers and alcohol consumers eating legumes less frequently.…”
Section: Legumes Consumption Among Young and Adult Residents In Sicilmentioning
confidence: 49%
See 1 more Smart Citation
“…'Overweight in parents' was relevant because among non-consumers of legumes were found more frequently obese or overweight subjects. Moreover numerous studies have shown that overweight in parents influences the child's eating behavior [18]. In our study individuals who practice physical activities consumed more frequently legumes, on the contrary smokers and alcohol consumers eating legumes less frequently.…”
Section: Legumes Consumption Among Young and Adult Residents In Sicilmentioning
confidence: 49%
“…There is also evidence for a positive association between education level and legumes intake [17], although graduates seem consume less legumes. Mothers' education level may be more important than fathers' ones for adolescent girls' eating behavior because mothers usually prepare meals, spend more time with the children and act as role models, especially for girls [18]. Elfhag and Linne [19] determine that eating pathology is shared by mothers and daughters, but not by sons.…”
Section: Legumes Consumption Among Young and Adult Residents In Sicilmentioning
confidence: 99%
“…SES, such as total family income, parental education, parental occupation, and family welfare determines food choices and access to ‘healthy’ and ‘unhealthy’ foods [ 19 ]. In studies regarding DP in adolescents, SES was identified as one of the main determinants of a healthy diet [ 14 , 17 , 21 , 22 , 23 ]; however, its influence is still little explored. DP that include a variety of healthy foods were directly or inversely associated to SES, and this association depended on the social context of each country [ 18 , 21 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for boys, eating attitudes and disorders are also associated with the evolution of weight, psychosocial well-beingpromoted by food (18) -, the strong appeal of socio-cultural worship of thinness (10) , the social group to which one belongs (19) , besides socioeconomic (10,20,21) and psychological (7) factors.…”
Section: Development Of Eating Behavior and Its Disordersmentioning
confidence: 99%